TRACING EARLY LITERACY DEVELOPMENT OF ELEMENTARY SCHOOL LOWER GRADES THROUGH RESPONDING TO ILLUSTRATED STORY BOOKS IN INDONESIAN CONTEXT - Hasanah, Muakibatul (IJRDO- Journal of Educational Research, 2016)
The research aims to describe the development of early reading and writing in lower grade of elementary school students. One way to explore these developments is through responding to illustrated story books that enable students to gain reading and writing in a natural atmosphere. The findings are the development of early reading and early writing ability in general grows gradually, and appreciation ability of illustrated story books for all grades is relatively constant and very good. The implications of the research conclusion are put forward, the teachers in grades 1-3 are expected to create child friendly literacy learning and need to be aware that students’ literacy (especially writing) develops gradually with varying levels of development, therefore, to be more tolerant of mistakes children made.